Beyond Collateral Damage : An Integrated Legal Framework For Civilian Protection in 2026 US-Israel-Iran Conflict - Budhiartie, Arrie; Pradhan, David H.; Dutta, Aruna; Panigrahi, Chandan; Asuhaimi, Farhanin binti Abdullah (Uti Possidetis: Journal of International Law, 2026)
Background: The 2026 armed conflict involving the United States, Israel and Iran raises difficult questions about civilian protection, particularly in relation to schools, hospitals, dual-use infrastructure, maritime passage, cyber disruption and nuclear-related facilities. Methodology: This article adopts normative legal research using statutory, conceptual and case-law approaches. It examines treaty law, customary international humanitarian law, international criminal law and state responsibility with reference to authoritative institutional materials from United Nations bodies, the ICRC, WHO, IAEA and IMO. Objectives: The article asks whether existing international legal rules provide adequate standards for assessing civilian harm in a technologically complex interstate conflict, and how those standards apply to protected institutions, dual-use infrastructure, maritime chokepoints and digital civilian dependency. Findings: The study finds that the principal difficulty is not normative absence, but the evidentiary and institutional fragility of applying distinction, proportionality, precautions, medical protection, humanitarian access and accountability under conditions of contested facts and restricted access. Originality/Novelty: The article contributes by treating civilian protection as an integrated legal architecture across attack, deprivation, movement, information infrastructure and responsibility.